Citizens in a Pluralistic Society and Bhineka Tunggal Ika - Ita Rustiati Ridwan; Irfan Fauzi (Yayasan Payungi Smart Madani, 2021)
Indonesia, which is a pluralistic country, has serious challenges to continue to maintain the unity and integrity of the nation. Seeing the reality of the Indonesian nation with its various diversity, the nation's founders agreed on the concept of Bhieka Tunggal Ika as the country's motto. In addition, the role of citizens in a pluralistic society in maintaining diversity in Indonesia is a very important study carried out by various parties. So, this study will examine in detail how the concept of citizenship in a pluralistic society and Bhineka Tunggal Ika. This research was conducted using literature studies by analyzing various sources from books, journals, and other references. This research can provide insight and knowledge for various parties in examining the concept of citizenship, pluralistic society and Bhineka Tunggal Ika.